The Functions and Mechanisms of the Cohesin Complex in Regulating the Fate Determinations of Stem Cells - Jianghong Xiang; Yihan Lai; Zuping He (Research)
Stem cells have important applications in both regenerative and reproductive medicine. The cohesin complex comprises 4 core subunits, namely, SMC1, SMC3, RAD21, and STAG, and notably, it plays pivotal roles in controlling the fate determinations of stem cells by facilitating the dynamic regulation of the 3-dimensional genome architecture. We have recently reported that RAD21 forms a complex with YAP1 and NEDD4 to promote the self-renewal of human spermatogonial stem cells and inhibit their apoptosis. In this review, we address the molecular properties of the cohesin complex and its multiple regulatory mechanisms in mediating the fate decisions of various kinds of stem cells, including hematopoietic stem cells, embryonic stem cells, spermatogonial stem cells, neural stem cells, and other types of stem cells. By maintaining the chromatin loop structure, the cohesin complex is involved in DNA repair and gene transcription, which in turn controls the pluripotency, self-renewal, and differentiation of stem cells. In addition, the cohesin complex ensures faithful DNA replication and sister chromatid cohesion, which indirectly supports genetic and epigenetic programs. Variants in the subunit components of the cohesin complex and proteins’ modifications further confer functional plasticity, and its mutations can lead to abnormal stem cell functions and are correlated with diseases including cancers. Future studies need to integrate multidisciplinary approaches including single-cell multi-omics and cryo-electronic microscopy to resolve the dynamic regulatory networks of the cohesin complex in stem cell fate regulation and further explore its potential applications in regenerative and reproductive medicine.